Aspergillus flavus native valve endocarditis following combined liver and renal transplantation: Case report and review of the literature. Issue 4 (26th April 2018) - Alsobayeg, Sultan; Alshehri, Nada; Mohammed, Shamayel; Fadel, Bahaa M.; Omrani, Ali S.; Almaghrabi, Reem S.
Abstract: Aspergillus endocarditis is a rare infection that occurs most commonly in patients with prior cardiac surgery but cases in post‐transplant recipients without prior cardiac surgery have been reported. Diagnosis is often delayed and requires high index of suspicion. We here report a case of Aspergillus endocarditis in solid organ transplant recipient.